Klasifikasi Status Keaktifan Siswa SMA di Jawa Barat Menggunakan Random Forest dengan SMOTE - M Itmamurohman; Pika Silvianti; La Ode Abdul Rahman (Xplore: Journal of Statistics, 2022)
The dropout rate in Indonesia has a higher percentage as education levels grow. The high school dropout rate in Indonesia is at 0.67%. West Java is the province with the highest high school dropout rate in the academic year 2017/2018. In the next academic year, the high school dropout rate in West Java decreased. The student who drop out of school was caused by various factors. This study examines important variables and classification performance that are generated by random forest. The number of dropout students is very small compared to the number of active students. The imbalance data is handled using SMOTE. Random forest with SMOTE is considered able to predict data classes better because it can increase sensitivity values and reduce errors in classifying dropout students as active students. Father's income, number of siblings, class, father's education level, and father's type of work are important variables that have a major influence in determining the active status of high school students in West Java.